FAKTOR YANG MEMPENGARUHI STUNTING PADA BALITA USIA 24-59 BULAN DI PUSKESMAS CEPU KABUPATEN BLORA - Elsa Nur Aini; Sri Achadi Nugraheni; Siti Fatimah Pradigdo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Stunting is a failure in children under five years due to chronic malnutrition so that children are too short of the WHO 2005 standard height, that is the z-score is less than -2SD or -3SD. The purpose of this study was to determine the risk factors for the incidence of stunting in infants aged 24-59 months in the working area of Cepu Health Center, Blora Regency. This study uses observational analytic studies with case control methods. The sample used was 76 toddlers consisting of 38 cases and 38 controls. The research instrument used was the method of recalling 2 x 24 hours of nutritional consumption and assisted with a list of URT to estimate the weight of food in grams. Data analysis using chi-square test. The results showed that the lack of level of energy sufficiency (OR=5,318, CI=1,997–14,163), the lack of maternal nutritional knowledge (OR=4,720, CI=1,790–12,450) and low family income per capita (OR= 5,385, CI=2,011–14,421) is a risk factor for the incidence of stunting in infants. Other factors in this study such as lack of protein adequacy (CI=0.167–1.928), history of low birth weight (LBW) (CI=0.318–5.219), history of ASI is not exclusive (CI=362–0,597), maternal education (CI= 0,315–31,946) and working mothers (CI=688–4,474) are not risk factors for stunting. Per capita family income is a risk factor that most influences the incidence of stunting in this study. It is expected that the Cepu Health Center can improve the nutritional knowledge of mothers and provide adequate energy nutritious food assistance, mothers under five provide the right nutrition according to the Nutrition Adequacy Rate of children under five, and the head of the family increases the income per capita of the family.